PKM EDUKASI PENANGANAN OSTEOARTRITIS BAGI IBU-IBU PKK RT 03 RW 05 KELURAHAN PEDALANGAN KECAMATAN BANYUMANIK - Abidin, Zainal; Purnomo, Didik; Kuswardani, Kuswardani (JPMUJ, 2026)
Increasing human age is a sign of decreasing tissue ability to repair itself, the older the human age, the body and physiological functions will also decrease so that there is a chance of getting non-communicable diseases such as osteoarthritis, especially in the knees. This community service (PKM) aims to provide assistance and training to prevent and treat knee pain caused by osteoarthritis, particularly in the knees of PKK RT 03 RW 05 mothers from Pedalangan Village, Banyumanik District. This PkM activity uses the method of providing counseling, conducting discussions and training to treat knee pain due to osteoarthritis. After the post-test, the results were obtained that 20 PKK RT 03 RW 05 mothers, Pedalangan Village, Banyumanik District, 100% understood how to prevent osteoarthritis and could transmit how to exercise to reduce pain due to osteoarthritis in the knees properly and correctly.